Some Factors that Influence Work-Life Balance of Workers - Muliawan Hamdani; Melati Mayang Sekar (Journal of Applied Business, Taxation and Economics Research, 2022)
In actual life, the efforts to achieve a harmonious balance between work and family life and other activities outside of work are very important. A balance between the both creates good mental health and it is condusive for personal life. Likewise for online motorcycle drivers (ojek online) with work activities that require them to leave home and family. Therefore, the study was conducted to ascertain several influencing factors of work-life balance. Some of the variables studied were Relation-Oriented Leadership Behavior, Personality, and Flexible Time Hours as independent variables and Work-Life Balance as the dependent variable. The object of this research was online motorcycle drivers who worked in Wonosobo Regency and 100 of them were selected as research samples. Through hypotheses testing by applying data processing software of SmartPLS 3, it was concluded that Relation-Oriented Leadership Behavior, Personality, and Flexible Time Hours positively influenced Work-Life Balance. Thus, all research hypotheses were accepted. Therefore, the better Relation-Oriented Leadership Behavior was performed, the better  Personality, and the better Flexible Time Hours was implemented, the better  Work-Life Balance of online motorcycle drivers in Wonosobo Regency.